Characteristic of Information and Communication Technology (ICT) innovation and its application: a descriptive study in Lhokseumawe City - Muhammad Fazil (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study analyses the characteristics of Information and Communication Technology (ICT) innovation in several districts in Aceh. This study was conducted in Lhokseumawe City. ICT has opened more accesses, shortened a long distance and made everything became closer as well as it has benefited us with more effective and useful time. Skill and competence to operate the Information and Communication Technology (ICT) tools could eventually provide all human beings with more simple and easy life. However, the availability of information and communication technology (ICT) provided by some governmental organizations in Aceh gave no positive impact on economic and social improvements to their communities, yet has led to another form of exclusivity and created an obvious technological gap where government remained working on a manual basis. This study employed descriptive qualitative approach using purposive sampling technique in selecting the participants. Data was collected through observation, interview and relevant document review. Data analysis was undergone through three steps using interactive methods: 1) Data reduction, 2) Display, and 3) Conclusion. The results showed that governance espouses to use Information and Communication Technology (ICT) system for every public sector although some other public sectors such as public policy, financial report and organization planning did not use it. While, the ICT system was incompatible at the government system. In addition, the result also found that ICT was not mutually integrated within the organization.